Data Analysis for the Life Sciences with R - Rafael A. Irizarry, Michael I. Love (CRC Press, Taylor & Francis Group, 2017)
This book covers several of the statistical concepts and data analytic skills needed to succeed in data-driven life science research. The authors proceed from relatively basic concepts related to computed p-values to advanced topics related to analyzing highthroughput data. They include the R code that performs this analysis and connect the lines of code to the statistical and mathematical concepts explained.